RELEVANSI JARIMAH HUDUD DAN HAM INTERNASIONAL DALAM IMPLEMENTASI DI ERA MODERN - Nairazi AZ (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
The Qur'anic concept of penal sanctions, especially criminal sanctions centered on hadd Because the existence of sanctions has been determined by syara '. Because after all the punishment applied to the perpetrator A form of justice for the victim, and impossible that man as a person can be separated with his community And this only occurs in the theoretical realm, but in the sociological reality Even in psychological reality, Human beings can not be separated from society In the concept of punishment formation in Islamic crime, the form of retribution (retaliation) includes two things are the violence of a punishment and the penalty imposed for a criminal offender In relation to the first aspect of the problems that arise later is the emergence of the view that the punishment demanded in Islamic criminal law is very cruel and ignores the human rights norms such as the form of hand-cutting penalty Stoning, crucifixion, cross-cutting of hands and feet and hanging. The forms of punishment are contrary to Article 7 of the International Covenant on Civil and Political Rights Where in the ICCPR (International Covenant on Civil and Political Rights) no one should be treated inhumanely Which has been agreed by various countries on the implementation of human rights If viewed from a Western perspective of human rights, hudūd is an example of punishment that violates the rules, prohibitions on treatment or punishment that they tend to deem humiliating and degrading human dignity And however the laws established in Islamic criminal law are backed by the social and political of the Islamic community at the time, which is also a response to its needs and interests.